KOMPUTASI EVOLUSIONER UNTUK MEMPREDIKSI ELEKTABILITAS PARTAI POLITIK PADA PEMILU 2014 DI INDONESIA - , ESA LINDA TAMAJATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
General Election Indonesia 2014 is coming up, many survey institutes have been running some surveys about political parties electability. It's interesting to know the electability of each political parties, so political parties electability prediction system for general election 2014 is needed to be developed as a statistical survey. Genetic Algorithms is computer program that simulate evolution process. Only strong individual that can survive, therefore in the evolution process, we expect to get the best individual. In this case, the population of chromosome that randomly generated made it possible to breed according to the evolution laws, if good chromosome breed, then good solution for the problem is expected as a result. General Election Indonesia 2014 is coming up, many survey institutes have been running some surveys about political parties electability. It's interesting to know the electability of each political parties, so political parties electability prediction system for general election 2014 is needed to be developed as a statistical survey.